Предмет: Алгебра, автор: minichvika2010

помогите пажешкаааааааа

Приложения:

Ответы

Автор ответа: othwqlmk
0

Ответ:

Объяснение:

1) \frac{x-3}{x+1}=0

ОДЗ: x\neq -1

x - 3 = 0

x = 3

2) \frac{x^{2}-16 }{x+4}=0

ОДЗ: x\neq -4

x^{2} -16=0

x^{2} =16

x = 4 (x\neq -4)

3 \frac{x+2}{x^{2} -4}=0

ОДЗ: x\neq -2; x\neq 2

\frac{x+2}{(x-2)(x+2)}=0

\frac{1}{x-2} =0

1 = 0

утверждение ложно

4) \frac{5}{x+7}-\frac{3}{x-7}=0

ОДЗ: x\neq -7; x\neq 7

\frac{5(x-7)-3(x+7)}{(x+7)(x-7)} =0

\frac{5x-35-3x-21}{(x+7)(x-7)} =0

\frac{2x-56}{(x+7)(x-7)}=0

2x - 56 = 0

2x = 56

x = 28

5) \frac{x+1}{x-4}=\frac{3x+1}{3x-1}

ОДЗ: x\neq 4; x\neq \frac{1}{3}

(x + 1)(3x - 1) = (3x + 1)(x - 4)

3x^{2} - x + 3x - 1 = 3x^{2} - 12x + x - 4

-x + 3x - 1 = -12x + x - 4

2x - 1 = -11x - 4

2x + 11x = -4 + 1

13x = -3

x = -\frac{3}{13}

6) \frac{9x-7}{3x-2}-\frac{4x-5}{2x-3}=1

ОДЗ: x\neq \frac{2}{3}; x\neq \frac{3}{2}

\frac{(2x-3)(9x-7)-(3x-2)(4x-5)}{(3x-2)(2x-3)}=1

\frac{18x^{2}-14x-27x+21-(12x^{2}-15x-8x+10)}{(3x-2)(2x-3)}=1

\frac{18x^{2}-14x-27x+21-(12x^{2}-23x+10)}{(3x-2)(2x-3)}=1

\frac{18x^{2} -14x-27x+21-12x^{2} +23x-10}{(3x-2)(2x-3)}=1

\frac{6x^{2} -18x+11}{(3x-2)(2x-3)}=1

6x^{2} - 18x + 11 = (3x - 2)(2x - 3)

6x^{2} - 18x + 11 = 6x^{2} - 9x - 4x + 6

-18x + 11 = -9x - 4x + 6

-18x + 11 = -13x + 6

-18x + 13x = 6 - 11

-5x = -5

x = 1

7) \frac{x^{2} + 20}{x^{2} -4}=\frac{x-3}{x+2}-\frac{6}{2-x}

ОДЗ: x\neq -2; x\neq 2

\frac{x^{2} +20}{x^{2} -4}-\frac{x-3}{x+2}+\frac{6}{2-x}=0

\frac{x^{2} +20}{(x-2)(x+2)} - \frac{x-3}{x+2} - \frac{6}{x-2}=0

\frac{x^{2}  +20-(x-2)(x-3)-6(x+2)}{(x-2)(x+2)}=0

\frac{x^{2} +20-(x^{2} -3x-2x+6)-6x-12}{(x-2)(x+2)}=0

\frac{x^{2} +20-(x^{2} -5x+6)-6x-12}{(x-2)(x+2)}=0

\frac{x^{2}+20-x^{2} +5x-6-6x-12 }{(x-2)(x+2)}=0

\frac{2-x}{(x-2)(x+2)}=0

\frac{-(x-2)}{(x-2)(x+2)}=0

-\frac{1}{x+2}=0

\frac{1}{x+2}=0

1 = 0

утверждение ложно

8) \frac{5}{x^{2} -7x}-\frac{x-5}{x^{2} +7} -\frac{9}{x^{2} -49}  =0

ОДЗ: x\neq 0; x\neq 7; x\neq -7

\frac{5}{x(x-7)}-\frac{x-5}{x(x+7)}-\frac{9}{(x-7)(x+7)}=0

\frac{5(x+7)-(x-7)(x-5)-9x}{x(x-7)(x+7)} =0

\frac{5x+35-(x^{2} -5x-7x+35)-9x}{x(x-7)(x+7)}=0

\frac{5x+35-(x^{2} -12x+35)-9x}{x(x-7)(x+7)}=0

\frac{5x+35-x^{2} +12x-35-9x}{x(x-7)(x+7)}=0

\frac{8x-x^{2} }{x(x-7)(x+7)}=0

\frac{x(8-x)}{x(x-7)(x+7)}=0

\frac{8-x}{(x-7)(x+7)}=0

8 - x = 0

-x = -8

x = 8

Похожие вопросы
Предмет: Қазақ тiлi, автор: maksatulyanuarbek54